Tourism development policy implementation in the natural tourism object of Tesbatan Waterfall, Kupang District - Hans A. Lao; Hamzah Nasarudin (Enrichment : Journal of Management, 2023)
The purpose of this study: 1) Knowing the ideal communication model for disseminating Kupang district government policies 2) Knowing the optimal resources in dealing with Tesbatan waterfall tourism development. 3) 3. Knowing the attitude of the ideal executor in order to be able to make policy implementation go well The research method uses a qualitative approach. The data sources used are primary and secondary data. Data collection techniques in this study were carried out through interviews, observation, and documentation. Data analysis was carried out in a qualitative descriptive method using the Miles & Huberman analysis model. This research seeks to obtain the ideal formulation of tourism policy implementation in the Tesbatan Waterfall tourism object based on four dimensions of public policy which is often called the Edward III model, which consists of communication, resources, implementing attitudes and bureaucratic structure.